Urinary biomarkers in the early diagnosis of diabetic kidney disease and diabetic retinopathy - Terzic, Brankica (Journal of Medical Biochemistry, 2025)
Introduction/Aim Urinary biomarkers are increasingly recognized as important indicators of renal injury in type 2 diabetes mellitus (T2DM), and some may also serve as early predictors of microvascular complications. Diabetic kidney disease (DKD) is the most common microvascular complication of type 2 diabetes mellitus and a leading cause of chronic kidney disease and end-stage renal failure. Although microalbuminuria is the established early marker of renal injury, its limited sensitivity and specificity necessitate novel urinary biomarkers for earlier detection. This study aimed to assess whether urinary type IV collagen, transferrin, and liver-type fatty acid–binding protein (L-FABP) could serve as early biomarkers of DKD and to evaluate their association with diabetic retinopathy. Methods Eighty T2DM patients were divided into two groups: normoalbuminuric (≤30 mg/day) and microalbuminuric (30–300 mg/day). Ten healthy individuals served as controls. All participants were older than 18 years, had diabetes duration >1 year, and an estimated glomerular filtration rate (eGFR) >60 ml/min/1.73 m². Urinary concentrations of type IV collagen, transferrin, and L-FABP were measured in 24-hour and first-morning urine samples using ELISA. Statistical analyses included group comparisons, correlation testing, and receiver operating characteristic (ROC) curve assessment. Results Urinary levels of all biomarkers were negligible in controls but significantly higher in microalbuminuric compared with normoalbuminuric patients (p < 0.05). Type IV collagen showed the highest diagnostic accuracy (90.4%) for early DKD. All biomarkers correlated positively with DKD, while urinary transferrin was additionally associated with diabetic retinopathy Conclusion Urinary type IV collagen, transferrin, and L-FABP are promising early biomarkers of diabetic kidney disease, demonstrating superior diagnostic potential to albuminuria. Moreover, urinary transferrin may serve as a noninvasive marker for early detection of diabetic retinopathy, supporting its role in monitoring microvascular complications in T2DM